Bankers' compensation: Sprint swimming in short bonus pools? - Esa Jokivuolle; Jussi Keppo (Bank of Finland, 2014)
The global financial crisis of 2007-2008 has given rise to new regulatory initiatives to put restrictions on the size and term of bankers' pay. We revisit the question whether these regulations are justified, both theoretically and empirically. We model bonuses as a series of sequential call options on profits and show that they provide the higher risk-taking incentives the shorter is the time between the payment points. However, using data on CEO bonuses at the end of 2006 and our model, we find no robust relationship between risk-taking incentives and US banks' stock returns during the global financial crisis. The crisis returns are related negatively to leverage and positively to the market to book equity ratio. Our findings suggest that regulating leverage would be more effective than regulating bankers' compensation.
URN:NBN:fi:bof-20140807153
Keywords: 330; Banking; bonuses; regulation; compensation